BERTAHANNYA BANGSAWAN LUWU (SUATU ANALISA BUDAYA POLITIK ORANG BUGIS) - Rismawidiawati Rismawidiawati (Balai Pelestarian Nilai Budaya Jawa Barat, 2016)
This article aims is to explain the reason of aristocratic group of Luwu still survive based on a review of political culture of the Bugis. This article presented in a descriptive analysis through the 4 (four) stages of historical research methods, namely the collection of resources (heuristic), criticism source of data, interpretation, and historiography. In addition, the technique of collecting data through interviews. The results found that the traditional political culture of the Bugis, known as siri 'na pesse make an important contribution to the survival of the aristocratic group of Luwu. This political culture present Tomanurung figure as a forerunner to the whole of kings and nobles in South Sulawesi included in Kedatuan Luwu. Luwu community believe that the descendants of Tomanurung destined to govern. If the ruling is not a descendant of Tomanurung, Luwu people believe that there will be a problem in the country. Apart from the assumption that the presence of this Tomanurung is a myth and as an invention of politics, the existences this character is the beginning of the birth of rulers / kings. The existence of Kedatuan Luwu which still exist today, although its function is not the same as in the past, as well as the elite dominated by the nobility (andi) Luwu is a picture that people still believe in the presence of royalty as the man who is destined to run the government.